Polygraphic studies. Issue 9 (September 1987) - Adamson, M
Abstract : Polygraphic recordings have provided new information about the wide ranges of normality in various diseases and the process of maturation from birth to childhood. New techniques will help to document clinical events accurately, improve diagnosis, and evaluate treatment.